2012
DOI: 10.1007/s11274-012-1067-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and characterization of antagonistic bacteria from tropical estuarine habitats of Cochin, India for fish health management

Abstract: Mortalities due to pathogenic bacteria are a major problem in aquaculture, especially in larval rearing systems. Use of antibiotics to overcome this problem is not an option any more due to the increasing antibiotic resistance among pathogens. The present study aims to understand the diversity of bacteria with antagonistic properties in the tropical estuarine habitats of Cochin, located along the southwest coast of India, and to use them as an alternative to antibiotics in aquaculture. Among the 4,870 isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…-NA, and TCBS produced 38, 32, and 27 isolates accounting for 15.26, 12.85, and 10.84 % respectively. 2216E was the best separation medium for bacterial recovery from coastal sediment and seafood samples, which may have been because 2216E is an exclusive medium for marine bacteria isolation and, when prepared with seawater containing a variety of metal ions and an appropriate salt, as opposed to distilled water, meant that 2216E was the closest match to the original growth environment of these marine microorganisms (Nair et al 2012). The majority of microorganisms from the …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-NA, and TCBS produced 38, 32, and 27 isolates accounting for 15.26, 12.85, and 10.84 % respectively. 2216E was the best separation medium for bacterial recovery from coastal sediment and seafood samples, which may have been because 2216E is an exclusive medium for marine bacteria isolation and, when prepared with seawater containing a variety of metal ions and an appropriate salt, as opposed to distilled water, meant that 2216E was the closest match to the original growth environment of these marine microorganisms (Nair et al 2012). The majority of microorganisms from the …”
Section: Resultsmentioning
confidence: 99%
“…Nutrient agar, as the experimental medium, was added to different substrates according to Nair et al (2012) with minor modifications, including skimmed milk for proteolytic activity, soluble starch for amylolytic activity, and 1 % Tween 80 for lipolytic activity, respectively. The hydrolytic exoenzymatic activity of the strains inoculated on the plates were observed after incubating at 28°C for 24 h. Proteolytic activity and lipolytic activity were judged by the transparent circle of milk degradation and the halo formation of precipitated fatty acids around the colony.…”
Section: Enzymatic Assaymentioning
confidence: 99%
“…Major molluscan pathogens such as Vibrio were shown to harbour a high number of mobile genetic elements (Hazen et al, 2010), showing their abilities to integrate elements that can increase their capacity to colonize an ecological niche. As antibiotics used in prophylaxis were banned to limit the development of bacterial resistance, antibiotic substitutes such as probiotics should not harbour antibiotic-resistant genes (Saarela et al, 2000;Nair et al, 2012). We therefore investigated the hCg-strains to ensure their antibiotic sensitivity to the common antibiotic used in aquaculture.…”
Section: Antibiotic Sensitivitymentioning
confidence: 99%
“…such as V. parahaemolyticus, V. nereis, V. vulnificus, V. alginolyticus, V. fluvialis, V. mediterranei and V. harveyi, confirming their potential application in aquaculture as antagonistic probiotics. Likewise, in recent studies, researchers identified six isolates of P. aeruginosa from estuarine habitats of Cochin, India for fish health management, and confirmed their antibacterial activity against the pathogenic species of Vibrio of fishes [33] . Toxicity assessments in brine shrimp showed pyocyanin to be non-toxic at concentrations up to 100 mg/L, and the LC 50 values were (296.65依18.15) mg/ L and (215.312依35.660) mg/L for the exposure times of 12 h and 24 h respectively.…”
Section: Discussionmentioning
confidence: 82%
“…However, recent findings indicated the growth of estuarine isolates of P. aeruginosa upto 50 g/L. Replacement of seawater by NaCl in the growth medium did not significantly inhibit growth and pyocyanin production [33] . All these findings support the well-adapted lineage with distinct ecophysiological features due to the cladogenic processes observed in environmental isolates of P. aeruginosa [34] .…”
Section: Discussionmentioning
confidence: 84%